Cooperative procedures and institutional mechanisms to promote compliance with the provisions of the Nagoya Protocol by CGIAR Centers: A submission from CGIAR Genebanks Accelerator - CGIAR Genebanks Accelerator (2025)
This short submission from CGIAR is in response to the call for submissions issued by the CBD Secretariat through Notification 2025-080 - “Submission of views to inform a preliminary review of the procedures and mechanisms on compliance under the Nagoya Protocol” (Ref.: SCBD/ABS/TS/KG/92324)